Perioperative Outcomes of Patients Undergoing Frame Based Stereotactic Brain Biopsies - Tanvir, Zermina; Rizwan, Muhammad; Shah, Zahid; Tanvir, Zunaira; Akhtar, Naveed; Jalal , Liaquat Ali (Biological and Clinical Sciences Research Journal, 2025)
Frame-based stereotactic brain biopsy is an established minimally invasive neurosurgical technique for obtaining tissue diagnosis of intracranial lesions, particularly when lesions are deep-seated or surgically inaccessible. Its safety and efficiency in resource-limited settings require continued local evaluation. Objective: To assess perioperative outcomes, including complication rates, operative time, and length of hospital stay in patients undergoing frame-based stereotactic brain biopsy at a tertiary care hospital in Pakistan. Methods: This descriptive cross-sectional study was conducted over six months from September 2024 to February 2025 at the Department of Neurosurgery, Nishtar Hospital, Multan. Ninety-seven patients aged 20 to 65 years who underwent frame-based stereotactic brain biopsy were enrolled using non-probability consecutive sampling. Demographic data, lesion characteristics, operative time, duration of hospital stay, and perioperative complications were recorded on a structured proforma. Data were analyzed using SPSS version 25. Quantitative variables were expressed as mean and standard deviation, while qualitative variables were presented as frequencies and percentages. Associations between complications and patient or lesion characteristics were assessed using the chi-square test, with p-values <0.05 considered statistically significant. Results: The mean age of patients was 46.7 ± 12.1 years, with a male-to-female Ratio of 1.5:1. The most common lesion locations were the frontal lobe (22.7%) and the parietal lobe (18.6%). Mean operative time was 46.2 ± 10.8 minutes, and the average hospital stay was 3.4 ± 1.6 days. Perioperative complications were observed in 14 patients (14.4 percent), including intracranial hemorrhage in 7 patients (7.2 percent) and new onset neurological deficits in 7 patients (7.2 percent). Higher complication rates were noted among older patients and those with deep-seated lesions, though these differences were not statistically significant (p > 0.05). Conclusion: Frame-based stereotactic brain biopsy is a safe and effective diagnostic procedure with acceptable operative time, short hospital stay, and low complication rates in a tertiary care setting in Pakistan. These findings support its continued use as a reliable neurosurgical diagnostic modality in resource-constrained environments.